Responsabilidade social na universidade: uma análise do projeto de extensão Leituras na Praça sob a luz das práticas sociais - Medeiros, Ana Paula de Oliveira (2020)
Society in general, NGOs and the government have exerted intense pressure for a socially responsible posture by organizations. In this context, Universities are included, as it is also up to them to develop their Social Responsibility (SR). Calderón, Gomes and Borges (2016) affirm that RS gained greater prominence in universities after the approval of the National Higher Education Assessment System (NHEAS), instituted in 2004, which inserted SR as one of the evaluation items of Brazilian HEIs. This research seeks to analyze the Readings in the Square Extension Project, carried out by the Federal University of Ceará, from the perspective of the Theory of Practice, with the Social Responsibility at the University (SRU) as a background. Such a project is an initiative that seeks to develop a reading public, promoting the reading of literary texts in the squares. Starting from the analysis nucleus of the practice itself, the objective of this research is to investigate the practices of project organization and reading as social practices. According to Reckwitz (2002), practice is the basic unit of analysis for understanding social reality. Therefore, we sought to investigate how such practices are configured, the elements that compose them (materials, meanings and competences), their relationships and how they develop, using the theoretical lens of Shove, Pantzar and Watson (2012). As for the methodological aspects, the qualitative approach was chosen with the realization of a case study. For data collection, direct observations, semi-structured interviews and document analysis were performed. For data analysis, the content analysis technique was used. The analyzes carried out showed that the practice of organizing the extension project is loaded with meanings such as, political act, possibility of discussing literary texts, exchange of knowledge, and others. As for the practice of reading, the data revealed that this practice proved to be quite consistent and occupies an important social function. It was identified that the importance given to reading and appreciation of literature are the main motivations that sustain this practice. Practitioners also demonstrate a strong concern with the occupation of public spaces and claim that from these practices new skills have been acquired. The research findings also revealed that the Readings in the square extension project has promoted the university's interaction with society and generated significant social benefits for practitioners and the surrounding community, fostering the university's socially responsible stance.